Investigation of regional development in Brazil: a patento-scientometric approach. (26th September 2019) - Motta, Gustavo Da Silva; Garcia, Pauli Adriano Da Almada; Azevedo-Ferreira, Maxwel De; Gomes, Mariana Passos Neves; Santos, Camila Carvalho Oliveira
Brazil's underdevelopment can be partly blamed on a low level of investments in research and development, causing its technology structure to be relatively backward in terms of innovation. The 'metal-mechanical complex', located in the South Fluminense Mesoregion (SFM) of the state of Rio de Janeiro, is recognised for its high economic importance to the country due to the presence of factories owned by large multinational and national companies and the corresponding group of firms supplying goods and services to them. The objective of this study was to assess the mesoregion's technological development through comparison of eight high-tech projects (four in the SFM and four in other parts of the state) that received financial support from the funding agency FAPERJ to produce innovative products or processes. This analysis first relied on computing scientometric and indicators and then involved comparing the efficiencies of the new firms by data envelopment analysis (DEA). The results revealed that the SFM, although highly industrialised, does not have a compatible level of technological development.